Feedback field control improves the precision of T2* quantification at 7 T. (5th July 2017) - Wyss, Michael; Duerst, Yolanda; Nanz, Daniel; Kasper, Lars; Wilm, Bertram Jakob; Dietrich, Benjamin Emmanuel; Gross, Simon; Schmid, Thomas; Brunner, David Otto; Pruessmann, Klaas Paul
Abstract : T 2 * mapping offers access to a number of important structural and physiological tissue parameters. It is robust against RF field variations and overall signal scaling. However, T 2 * measurement is highly sensitive to magnetic field errors, including perturbations caused by breathing motion at high baseline field. The goal of this work is to assess this issue in T 2 * mapping of the brain and to study the benefit of field stabilization by feedback field control. T 2 * quantification in the brain was investigated by phantom and in vivo measurements at 7 T. Repeated measurements were made with and without feedback field control using NMR field sensing and dynamic third‐order shim actuation. The precision and reliability of T 2 * quantification was assessed by studying variation across repeated measurements as well as fitting errors. Breathing effects were found to introduce significant error in T 2 * mapping results. Field control mitigates this problem substantially. In a phantom it virtually eliminates the effects of emulated breathing fluctuations in the head. In vivo it enhances the structural fidelity of T 2 * maps and reduces fitting residuals along with standard deviation. In conclusion, feedback field control improves the fidelity of T 2 * mapping in the presence of field perturbations. It is an effective means of countering bulk susceptibility effects of breathing and hence holds particular promise for efforts to leverage high field for T 2 * studies in vivo . Abstract : Quantitative T 2 * contrast is inherently sensitive to magnetic field variations and requires a spatially homogeneous and temporally stable magnetic field. The effect of field perturbations on T 2 * quantification in the brain and the benefit of field stabilization using a real‐time correction approach were evaluated. Feedback field control reduces respiration‐induced field changes. The consequential decrease of the artifact level in the T 2 *‐weighted source images translates into better and more reliable measurements as well as an improved fit quality in T 2 * quantification.